2019
DOI: 10.1111/pin.12771
|View full text |Cite
|
Sign up to set email alerts
|

ANXA10 induction by interaction with tumor‐associated macrophages promotes the growth of esophageal squamous cell carcinoma

Abstract: Tumor‐associated macrophages (TAMs) have important roles in the growth, angiogenesis and progression of various tumors. Although we have demonstrated the association of an increased number of infiltrating CD204+ TAMs with poor prognosis in esophageal squamous cell carcinomas (ESCCs), the roles of TAMs in ESCC remain unclear. Here, to study the effects of TAMs on the tumor microenvironment of ESCCs, we established a co‐culture assay using a human ESCC cell line and TAM‐like peripheral blood monocyte‐derived mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…Another limitation of this study is that the specific role of ANXA10 in SBA was not examined. The function of ANXA10 has been reported in several organs (13,14,20,21). In CRCs, ANXA10 expression has been correlated with microsatellite instability (21) and involves BRAF mutation and CpG island methylation (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of this study is that the specific role of ANXA10 in SBA was not examined. The function of ANXA10 has been reported in several organs (13,14,20,21). In CRCs, ANXA10 expression has been correlated with microsatellite instability (21) and involves BRAF mutation and CpG island methylation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several carcinomas have been reported to express ANXA10, including carcinomas of the liver (12), gastrointestine (11), and oesophagus (13). We have previously reported that ANXA10 is associated with the gastric phenotype of gastric cancer through the regulation of pancreatic duodenal homeobox-1 (PDX1) (14) and that ANXA10 is associated with early-stage gastric cancer (15).…”
mentioning
confidence: 99%
“…Immunohistochemical staining was performed according to several previous methods with some modifications including a western blotting study [ 5 , 8 ]. Paraffin-embedded tissue blocks were available for immunohistochemical evaluation in 103 representative slides.…”
Section: Methodsmentioning
confidence: 99%
“…105 CD204 + TAM can also increase the expression of tumor suppressor protein annexin A10 (ANXA10) in cancer cells, and promote the proliferation of ESCC cells through phosphorylation of Akt and Erk1/2 pathways. 106 The high expression of ANXA10 in cancer cells has been found to promote cancer cell growth and proliferation in a variety of tumors including lung cancer, 107 ovarian cancer, 108 and prostate cancer. 109 Indeed, various secreted factors such as Cyr61, 105 GDF15, 100,101,110 TGF-βRII, 100,111,112 and ANXA10 106 have been reported to be associated with poor prognosis of ESCC.…”
Section: Tumor-associated Macrophages (Tams)mentioning
confidence: 99%
“…106 The high expression of ANXA10 in cancer cells has been found to promote cancer cell growth and proliferation in a variety of tumors including lung cancer, 107 ovarian cancer, 108 and prostate cancer. 109 Indeed, various secreted factors such as Cyr61, 105 GDF15, 100,101,110 TGF-βRII, 100,111,112 and ANXA10 106 have been reported to be associated with poor prognosis of ESCC. This series of studies revealed that TAMs could promote ESCC progression through strong secretory functions, and demonstrated the huge potential of TAMs-related pathways and molecules as novel therapeutic targets and biomarkers.…”
Section: Tumor-associated Macrophages (Tams)mentioning
confidence: 99%